A comparison of the stem cell characteristics of murine tenocytes and tendon-derived stem cells - Katie Joanna Lee; Peter David Clegg; Eithne Josephine Comerford; Elizabeth Gail Canty-Laird (BMC Musculoskeletal Disorders, 2018)
Abstract Tendon is a commonly injured soft musculoskeletal tissue, however, poor healing potential and ineffective treatment strategies result in persistent injuries and tissue that is unable to perform its normal physiological function. The identification of a stem cell population within tendon tissue holds therapeutic potential for treatment of tendon injuries. This study aimed, for the first time, to characterise and compare tenocyte and tendon-derived stem cell (TDSC) populations in murine tendon. Tenocytes and TDSCs were isolated from murine tail tendon. The cells were characterised for morphology, clonogenicity, proliferation, stem cell and tenogenic marker expression and multipotency. TDSCs demonstrated a rounded morphology, compared with a more fibroblastic morphology for tenocytes. Tenocytes had greater clonogenic potential and a smaller population doubling time compared with TDSCs. Stem cell and early tenogenic markers were more highly expressed in TDSCs, whereas late tenogenic markers were more highly expressed in tenocytes. Multipotency was increased in TDSCs with the presence of adipogenic differentiation which was absent in tenocytes. The differences in morphology, clonogenicity, stem cell marker expression and multipotency observed between tenocytes and TDSCs indicate that at least two cell populations are present in murine tail tendon. Determination of the most effective cell population for tendon repair is required in future studies, which in turn may aid in tendon repair strategies.